2007
DOI: 10.5713/ajas.2007.556
|View full text |Cite
|
Sign up to set email alerts
|

Chito-oligosaccharides as an Alternative to Antimicrobials in Improving Performance, Digestibility and Microbial Ecology of the Gut in Weanling Pigs

Abstract: A total of 126 crossbred weanling pigs (average body weight of 6.3±0.3 kg) were used to investigate the effect of chitooligosaccharide (COS) on growth performance, nutrient digestibility, pH of gastro-intestinal tract (GI), intestinal and fecal microflora of young piglets. Pigs were allocated to three dietary treatments based on body weight and gender in a single factorial arrangement. Treatments were control (No COS), T1 (0.2% COS during starter (6-13 kg) and 0.1% COS during grower (13-30 kg) phases, and T2 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
43
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 28 publications
7
43
1
Order By: Relevance
“…Although positive effects have been reported on poultry consuming chitosan or buckwheat alone (Hirano et al, 1990;Razdan & Pettersson, 1994;Kondo & Osad 1996;Tanaka et al, 1997;Mei 2011), this is the first report on positive lipid profile-changing effects of buckwheat with trace amounts of chitosan. Several animal studies have confirmed that supplementing chitosan at up to 50 g/kg in feed has no negative effects on the growth and feed intake of the treated animals (Kobayashi et al, 2002;2006;Han et al, 2007;Hossain & Blair, 2007;Khambualai et al, 2009;Yan & Kim, 2011). Results in the present study agree with those findings as no detrimental effects of chitosan at up to 500 mg/kg were recorded.…”
Section: Discussionsupporting
confidence: 83%
“…Although positive effects have been reported on poultry consuming chitosan or buckwheat alone (Hirano et al, 1990;Razdan & Pettersson, 1994;Kondo & Osad 1996;Tanaka et al, 1997;Mei 2011), this is the first report on positive lipid profile-changing effects of buckwheat with trace amounts of chitosan. Several animal studies have confirmed that supplementing chitosan at up to 50 g/kg in feed has no negative effects on the growth and feed intake of the treated animals (Kobayashi et al, 2002;2006;Han et al, 2007;Hossain & Blair, 2007;Khambualai et al, 2009;Yan & Kim, 2011). Results in the present study agree with those findings as no detrimental effects of chitosan at up to 500 mg/kg were recorded.…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies investigating the effects of COS on nutrient digestibility have been variable. Han et al (2007) Table 4 The effect of COS supplementation at different MW on faecal lactic acid bacteria and Escherichia coli populations (least square means and s.e.) Means with the same superscript alphabets within rows are not significantly different (P .…”
Section: Discussionmentioning
confidence: 99%
“…This pronounced effect for piglet growth seems to be related the ability of COS to act as a selective agent for gut bacteria, inhibiting the proliferation of noxious bacteria such as E. coli or Bacillus cereus (HAN et al, 2007;KUMAR et al, 2007;XIAO et al, 2014). This may be favorable for performance due to a reduction in the incidence of diarrhea (HAN et al, 2007;XU et al, 2013;WANG et al, 2012). In the present study, there was no significance for diarrhea because of the reduced sanitary challenge, reducing the benefits of COS. (PINHEIRO et al, 2006).…”
Section: Resultsmentioning
confidence: 52%
“…The lesion score average, intestinal morphometry, goblet cell numbers, and inflammatory cells were used in the statistical analysis with 30 fields per segment and Chitooligosaccharide for piglets: effects on performance, viscera and intestinal morphometry (HAN et al, 2007;XU et al, 2013;WANG et al, 2012), with good results right after weaning. This pronounced effect for piglet growth seems to be related the ability of COS to act as a selective agent for gut bacteria, inhibiting the proliferation of noxious bacteria such as E. coli or Bacillus cereus (HAN et al, 2007;KUMAR et al, 2007;XIAO et al, 2014). This may be favorable for performance due to a reduction in the incidence of diarrhea (HAN et al, 2007;XU et al, 2013;WANG et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation